Fatigue life on a full scale test rig: Forged versus cast wind turbine rotor shafts. Issue 7 (September 2016) - Herrmann, J; Rauert, T; Dalhoff, P; Sander, M
Abstract: To reduce uncertainties associated with the fatigue life of the highly safety relevant rotor shaft and also to review today's design practice, the fatigue behaviour will be tested on a full scale test rig. Until now tests on full scale wind turbine parts are not common. Therefore, a general lack of experience on how to perform accelerated life time tests for those components exists. To clarify how to transfer real conditions to the test environment, the arrangements and deviations for the upcoming experimental test are discussed in detail. In order to complete investigations of weight saving potentials, next to getting a better comprehension of the fatigue behaviour by executing a full scale test, a further outcome are suggestions for the usage of cast and forged materials regarding the fatigue and the remaining life of the rotor shaft. It is shown, that it is worthwhile to think about a material exchange for the forged rotor shaft.